Plant Source Derived Compound Exhibited In Silico Inhibition of Membrane Glycoprotein In SARS-CoV-2: Paving the Way to Discover a New Class of Compound For Treatment of COVID-19 - Mahanta, Saurov; Naiya, Tufan; Biswas, Kunal; Changkakoti, Liza; Mohanta, Yugal Kishore; Tanti, Bhaben; Mishra, Awdhesh Kumar; Mohanta, Tapan Kumar; Sharma, Nanaocha (Frontiers in Pharmacology, 2022)
SARS-CoV-2 is the virus responsible for causing the COVID-19 disease in human, which is creating the recent pandemic across the world, where lower production of type I interferon (IFN-I) is associated with the deadly form of the disease. Membrane protein or SARS-CoV-2 M proteins are known to be the major reason behind the lower production of human IFN-I by suppressing the expression of IFNβ and Interferon Stimulated Genes. In this study, 7832 compounds from 32 medicinal plants of India having traditional knowledge linkage with pneumonia like disease treatment, were screened against the Homology Modelled structure of SARS-CoV-2 M protein with the objective to identify some active phytochemical as inhibitors. The entire study was carried out using different modules of Schrodinger Suite 2020-3. During the docking of the phytochemicals against the SARS-CoV-2 M protein, a compound, ZIN1722 from Zingiber officinale showed the best binding affinity with Glide Docking Score of -5.752 and Glide gscore of -5.789. In order to study the binding stability, the complex between the SARS-CoV-2 M protein and ZIN1722 was subjected to 50ns Molecular Dynamics simulation using Desmond module of Schrodinger suite 2020-3, during which the receptor ligand complex showed substantial stability after 32 ns of MDs. The molecule ZIN1722 also showed promising results during ADME-Tox analysis performed using Swiss ADME and pkCSM. With all the findings of this extensive computational study, the compound ZIN1722 is proposed as potential inhibitor to the SARS-CoV-2 M protein, which may subsequently prevent the immunosuppression mechanism during the SARS-CoV-2 virus infection in the human body. Further studies based on this work would pave the way towards identification of an effective therapeutic regime for the treatment and management of SARS-CoV-2 infection in a precise and sustainable manner.